2021
DOI: 10.7150/ijbs.50773
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of Autophagy-Related MicroRNAs in Cancer

Abstract: Autophagy is a conserved catabolic process involving the degradation and recycling of damaged biomacromolecules or organelles through lysosomal-dependent pathways and plays a crucial role in maintaining cell homeostasis. Consequently, abnormal autophagy is associated with multiple diseases, such as infectious diseases, neurodegenerative diseases and cancer. Currently, autophagy is considered to be a dual regulator in cancer, functioning as a suppressor in the early stage while supporting the growth and metasta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 199 publications
0
38
0
Order By: Relevance
“…Abnormal regulation of miRNA plays an important role in tumorigenesis and development [5,6]. During the occurrence and development of different types of human cancers, miRNAs consider an oncogene or tumor suppressor gene in the occurrence and development, respectively [5,6]. The application of miRNAs in the diagnostic classi cation and prognostic evaluation of thyroid cancer has been a research hotpot in recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal regulation of miRNA plays an important role in tumorigenesis and development [5,6]. During the occurrence and development of different types of human cancers, miRNAs consider an oncogene or tumor suppressor gene in the occurrence and development, respectively [5,6]. The application of miRNAs in the diagnostic classi cation and prognostic evaluation of thyroid cancer has been a research hotpot in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring the potential molecular mechanisms of thyroid cancer is particularly important for treating patients. MicroRNA (miRNA), an additional product produced during gene transcription, not only plays an important role in cell morphology, structure, and functional transformation by participating in epigenetic, transcriptional, and post-transcriptional regulation, but also plays an important role as an oncogene or tumor suppressor gene in the occurrence and development of malignant tumors, including thyroid cancer [4][5][6]. More and more studies have con rmed that miR-32-5p plays a very important role in the occurrence and development of different malignant tumors in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Given their well-known contributions to cell death control [ 36 ] and autophagy [ 37 ], miRNAs may easily be envisioned to play key roles in the processes regulating ICD.…”
Section: Epigenetic Regulation Of Icd-hallmarks By Mirnamentioning
confidence: 99%
“…It has been reported that autophagy plays an essential role in the maintenance of cellular RNA homeostasis by degrading several types of RNAs, including miRNAs. 79 , 80 Autophagy could regulate miRNA homeostasis by degradation via the selective autophagy receptor calcium binding and coiled-coil domain 2 (CALCOCO2), targeting the miRNA machinery factors dicer 1, ribonuclease type III (DICER1), and argonaute RNA-induced silencing complex (RISC) component 1/argonaute-1 (EIF2C1/AGO1). 81 The inhibition of autophagy can decrease miRNA levels and lead to the depression of miRNA activity, which suggests that autophagy acts as a checkpoint for the maintenance of miRNA abundance and activity.…”
Section: Autophagy-related Circrna In Cancermentioning
confidence: 99%